Reviving the Modern Architecture of Arieh Sharon’s Obafemi Awolowo University, Ilé-Ifẹ̀ , Nigeria - Babatunde Jaiyeoba; Bayo Amole (Docomomo Journal, 2023)
Obafemi Awolowo University (OAU), Ilé-Ifẹ̀, Nigeria, was established after Nigeria’s independence in 1960 as the University of Ife. Bauhaus architecture school graduate Arieh Sharon (1900-1984) designed the master plan and most of the initial buildings in the university core through Israeli-Nigerian technical development relations. The often written about campus is one of the most prominent modern architectural exemplars in Africa and one of the exhibits during the one-hundred-year celebration of Bauhaus–Bauhaus 100–in 2019. Like many examples of modern architecture around the world, this campus needs conservation measures for various reasons, including being out of contemporary functional use. However, this campus is in intensive use; in fact, the expanding use and minimal awareness of inherent values coupled with maintenance issues are the major reasons for conservation measures. Local and international collaboration of concerned partners resulted in the Conservation Management Plan (CMP) of the Ilé-Ifẹ̀ campus being one of the 13 projects funded by the Getty Keeping-It-Modern (KIM) 2020 program with complementary measures funded by Gerda Henkel Stiftung. This paper details the actions taken so far in conserving the unique modern architecture of the university and the future actions needed to ensure it continues to occupy its place in architectural discourse.